Semiquantitative multi‐analysis of plasma obtained from Romney lambs (Ovis aries) by inductively coupled plasma mass spectrometry, and the classification according to feed type. (17th January 2013) - Takahashi, Fumihito; Mochizuki, Mariko; Sato, Touko; Katayama, Kinya; Kenyon, Paul R.; Morris, Stephen T.; Kemp, Peter D.; Ozawa, Takeyuki; Ueda, Fukiko; Tazaki, Hiroyuki
Abstract The establishment of a classification system for domestic animals on consumed feed stuff is thought to be important from both a hygiene and market point of view. We collected plasma samples of Romney lambs (Ovis aries) which were fed one of the following: a herb‐clover mix (n = 10) which included chicory, red clover, white clover and plantain; a plant‐grass mix (n = 10) which included plantain, ryegrass and white clover; or a grass mix (n = 10) which included ryegrass and white clover. A total of 20 elements in plasma samples obtained from the lambs were analyzed using inductively coupled plasma mass spectrometry. The data were then analyzed by principal component analysis. The lambs were divided into three groups on a score plot depending on the different feed conditions. Furthermore, discriminant analyses of the elements were examined, using linear discriminant analysis with forward stepwise regression. This discriminant function correctly classified the samples from each group. The accuracy of classification of each group, as shown by 10‐fold cross‐validation, proved the effectiveness of the established discriminant function. It is concluded that using linear discriminant analysis might be a useful tool for the validation of elements from plasma in lambs grown in different conditions.